Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Pembatasan Cairan Pada Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa Di Ruang Hemodialisa RSUD Raja Ahmad Tabib Provinsi Kepri - Darmawati Darmawati; Indah Purnama Sari; Rizki Sari Utami (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
WHO (World Health Organization) data for 2020 is one of the main health problems in the world, globally around 1 in 10 of the world's population is identified as chronic kidney disease. The aim of this research is to determine the factors associated with compliance with fluid restrictions in chronic kidney failure patients undergoing hemodialysis in the hemodialysis room at Raja Ahmad Tabib Hospital, Riau Islands Province. This type of research is quantitative descriptive with a cross sectional approach. The sample in this study consisted of 48 people. Data collection methods and tools use questionnaires. The conclusion from the data analysis is that there is a significant relationship between family support and compliance with fluid restrictions in chronic kidney failure patients undergoing hemodialysis with a significant value of 0.007<0.05, there is a relationship between staff support and compliance with fluid restrictions with a sig p value of 0.000<0, 05 and there is a relationship between the length of HD and compliance with fluid restrictions with a sig p value of 0.000 <0.05 in the Chi Square test. Suggestion: it is hoped that this research can increase knowledge regarding compliance with fluid restrictions in chronic kidney failure patients undergoing hemodialysis, so that respondents can minimize the occurrence of complications due to excess fluid.